2007
DOI: 10.2135/cropsci2006.12.0827
|View full text |Cite
|
Sign up to set email alerts
|

Within‐Boll Yield Components of High Yielding Cotton Cultivars

Abstract: Cotton (Gossypium hirsutum L.) within‐boll yield components have changed throughout the last 30 yr of cultivar development. The question arises, how do within‐boll yield components differ in contemporary high yielding cultivars? Nine commercially available cotton cultivars were over‐seeded and hand‐thinned to 10.8 plants m−2 in 2001, 2002, and 2003. Before machine harvest, plants from 6 m of one row were removed from each plot and hand‐harvested by fruiting position. After hand‐harvest, seed cotton from each f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 9 publications
1
35
0
Order By: Relevance
“…When grown in these environments with four N application levels the varieties of the respective seed‐size classes produced fuzzy seed that differed in mean weight (Table 2). Lint yields and mean seed size of commercial cotton varieties have varied inversely for the past 60 yr (Culp and Harrell, 1975; Harrell and Culp, 1976; Bednarz et al, 2007), apparently in response to selection for high lint percentage and lint yield. Highest lint yields were observed in these experiments when varieties were of a medium seed size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When grown in these environments with four N application levels the varieties of the respective seed‐size classes produced fuzzy seed that differed in mean weight (Table 2). Lint yields and mean seed size of commercial cotton varieties have varied inversely for the past 60 yr (Culp and Harrell, 1975; Harrell and Culp, 1976; Bednarz et al, 2007), apparently in response to selection for high lint percentage and lint yield. Highest lint yields were observed in these experiments when varieties were of a medium seed size.…”
Section: Resultsmentioning
confidence: 99%
“…Such a result could accrue from simple selection for high gin turnout, the fraction of lint obtained from harvested seed cotton. In fact the mean seed size of cotton varieties has been decreasing for the last 30 yr (Bednarz et al, 2007).…”
mentioning
confidence: 99%
“…Non-additive gene action for fiber quality traits, including fiber length, fiber strength and micronaire value, have been reported by Khan et al (1991), Baloch et al (1997) and Hassan et al (2000). Cheatham et al (2003) indicated that lint percentage and fiber strength exhibited primarily additive genetic effects, while micronaire and length exhibited primarily dominant genetic effects. The result of the half-diallel analysis showed that LP exhibited additive and dominant genetic effects, with the dominant effect being primary.…”
Section: Discussionmentioning
confidence: 98%
“…However, the negative and non-significant association between strength and LP, L/S, L/SAS, F/S, and F/SAS for interspecific F 1 cotton populations shows the complex interrelationship of fiber strength with lint yield components. It seems logical that the ultimate way to increase yield per boll is to increase the number of fibers produced, since fibers produced per seed has the greatest effect on lint yield (Bednarz et al, 2007;Rauf et al, 2007). A negative and significant correlation of UI with F/S and F/SAS shows that increasing the number of fibers borne on seeds leads to more variability in the length of fibers (Basal and Smith, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation